Emotional appeals and news values as factors of shareworthiness in Ice Bucket Challenge coverage. Issue 2 (7th February 2020) - Kilgo, Danielle K.; Lough, Kyser; Riedl, Martin J.
Abstract : The 2014 amyotrophic lateral sclerosis Ice Bucket Challenge (IBC) received unprecedented attention by both news media and social media audiences. Using content analysis, this research examines how digital news utilized different news values and emotional appeals to cover the IBC. In addition, this work includes a secondary analysis that examines what coverage characteristics influenced social media audiences to share content on Facebook and Twitter. Results reveal that while celebrity participation and human interest stories were more likely to be covered, news values played a limited role in predicting audience sharing practices. Articles that use emotions in a story are more likely to entice sharing on Facebook than on Twitter.